UPAYA PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MELALUI CREATIVE PROBLEM SOLVING PADA SISWA KELAS VIII SEMESTER GANJIL SMP NEGERI 1 BANDAR LAMPUNG - Haryanto; Alamsyah (Prodi Pendidikan Matematika, STKIP PGRI Bandar Lampung, 2019)
The research problem is the low mathematical problem solving abilities of students. With this, the purpose of the study was to improve problem solving skills through Creative Problem Solving in the eighth grade students of the odd semester of SMP Negeri 1 Bandar Lampung. This research is a classroom action research (CAR). The research subjects were class VIIIB students of SMP Negeri 1 Bandar Lampung. The research data was taken using tests with indicators of success if 70% of students had passed the minimum completeness criteria or students had scored more than or equal to 70. From the results of the study the students' mathematical problem solving abilities in the first cycle were 60.98, in the second cycle of 70.74, and the third cycle of 77.97. Thus the completeness of students' mathematical problem solving abilities from cycle I to cycle II has increased by 9.76 and from cycle II to cycle III has increased 7.23. With this, it can be concluded that there is an increase in problem solving skills through Creative Problem Solving.